Estimating road transport costs between EU regions - Damiaan Persyn; Jorge Diaz-Lanchas; Javier Barbero (European Commission, Joint Research Centre (JRC), 2019)
Transport costs are a crucial element of any spatial economic model. Surprisingly, good transport cost estimates at a detailed spatial level for the EU are not readily available. In this paper we address this issue by estimating a novel dataset of road freight transport costs for goods for the EU regions at the NUTS 2 level. In the spirit of the generalized transport cost (GTC) concept, we calculate the composite cost related to distance and time for the optimal route of a representative truck. We consider routes between large random samples of centroids drawn from a 1kmx1km population density grid. These transport costs are averaged to obtain an origin-destination cost matrix (in euros) at the region-pair level. The sampling approach also allows calculating the average transport cost within the regions. We separately report the corresponding iceberg transport costs for each pair of European regions, since this is the form of input required by many economic models. We also consider the effect of changes in the components of the GTC in order to evaluate transport policies. We set up a transport policy tool to assess the impact of road-transport infrastructure investment in a region by considering upgrading roads to highways. We apply this tool to study transport infrastructure investment through the European Cohesion Policy program 2014-2020.
Keywords: R11; R12; R40; R41; 330; Rhomolo; Region; Growth; Generalized Transport Costs; Infrastructure; Cohesion Policy; OSM; EU